2016
DOI: 10.5901/mjss.2016.v7n5p361
|View full text |Cite
|
Sign up to set email alerts
|

Hosts’ Perception of Impacts of Community Development Schemes and Tourism Projects In Southeast Nigeria

Abstract: Recently

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Elsewhere, Agboeze and Nwankwo (2016) carried out an ethnographic study on hosts' perception of impacts of community development. According to the study, indigenous communities have been adversely affected by underdevelopment that can be traced to the remoteness of their physical environment and the apparent concentration of resources in the urban areas.…”
Section: Review Of Extant Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Elsewhere, Agboeze and Nwankwo (2016) carried out an ethnographic study on hosts' perception of impacts of community development. According to the study, indigenous communities have been adversely affected by underdevelopment that can be traced to the remoteness of their physical environment and the apparent concentration of resources in the urban areas.…”
Section: Review Of Extant Literaturementioning
confidence: 99%
“…Finally, the study revealed that developmental plans could facilitate migration into the communities, which can in turn negatively impact on the communities' 'carrying capacities'. In conclusion, the study blames this negative perception on poor orientation, lack of participatory mechanism, poor stakeholders' consultation, inadequate management skills and total disregard for the indigenous value system (Agboeze & Nwankwo, 2016).…”
Section: Review Of Extant Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…It can serve as a veritable tool through which cultural elements of the host community move to another cultural setting. In the same vein, tourism opens the door of interaction for the host community to meet people of different cultural background, make new friends which foster social cohesion, learn about the world, and expose themselves to new perspectives (Agboeze & Nwankwo, 2016). Experiencing different cultural practices enriches experiences, broadens horizons, and increases insight and appreciation for different approaches to living (Ojo, 2014;Agboeze & Nwankwo, 2016).…”
Section: Background Of the Studymentioning
confidence: 99%
“…In the same vein, tourism opens the door of interaction for the host community to meet people of different cultural background, make new friends which foster social cohesion, learn about the world, and expose themselves to new perspectives (Agboeze & Nwankwo, 2016). Experiencing different cultural practices enriches experiences, broadens horizons, and increases insight and appreciation for different approaches to living (Ojo, 2014;Agboeze & Nwankwo, 2016). Olumirin waterfall is a tourism centre located in Erin-Ijesa town in Oriade Local Government, Osun state.…”
Section: Background Of the Studymentioning
confidence: 99%